2001
DOI: 10.1061/(asce)0733-9399(2001)127:7(646)
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche Statistics of Interface Crack Propagation in Fiber Bundle Model: Characterization of Cohesive Crack

Abstract: This paper considers a model of crack propagation taking place at the interface between a rigid support and an elastic plate. The interface is modeled using a fiber bundle model (i.e., describing a damage behavior using a discrete set of elastic brittle elements having a random strength). This paper studies the fluctuations of the force required to propagate the crack along the interface. The statistics of avalanches, defined as a series of elements that are broken simultaneously under a load that decreases wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 10 publications
7
38
0
1
Order By: Relevance
“…It corresponds for instance to diffusion controlled dissolution processes. Interpreting the results in [11], it is shown that the size of the fracture process zone increases with increasing porosity in accordance with experimental observations [12]. The creep -fracture interaction is analyzed in the second part of the paper.…”
Section: Introductionsupporting
confidence: 71%
See 3 more Smart Citations
“…It corresponds for instance to diffusion controlled dissolution processes. Interpreting the results in [11], it is shown that the size of the fracture process zone increases with increasing porosity in accordance with experimental observations [12]. The creep -fracture interaction is analyzed in the second part of the paper.…”
Section: Introductionsupporting
confidence: 71%
“…There are also a number of studies that may be placed among the two extremes that global and local load-sharing rules constitute. Among them is the study by Delaplace et al [11], who constructed an hierarchically connected fiber bundle model. They have worked out analytically and numerically the statistics of avalanches in a system whose geometry mimics the propagation of crack front at the interface between a rigid support and an elastic beam.…”
Section: Zip Model -Case Of Interface With Variation Of Porositymentioning
confidence: 99%
See 2 more Smart Citations
“…In order to follow the crack front as the breakdown process develops, we implement the "conveyor belt" technique [21,34]. We illustrate this technique in Figure 2.…”
Section: Model and Methodsmentioning
confidence: 99%